Literasi Digital terhadap Perilaku Penggunaan Internet Berkonten Islam di Kalangan Remaja Muslim Kota - Millenia Prihatini; Abdul Muhid (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Internet as media and information technology not only has a positive impact but also harms its users. Teenagers are the most vulnerable group that has an impact on internet use. The impact of using the internet depends on the digital literacy level of its users. This study examines digital literacy's effect on using the internet with Islamic content among urban Muslim teenagers. This study uses a quantitative approach with a survey method. The research subjects were 500 urban adolescents as the research sample. Measuring instruments used in this study are the Digital Literacy Scale for Teenagers to measure digital literacy and the Internet Behaviors Scale to measure internet usage behaviour. The result showed that digital literacy had a significant positive effect on internet usage behavior (B = 0.314; t = 13.602; p = 0.000). The higher level of digital literacy of adolescents automatically makes the higher behaviour in using the internet shows that digital literacy is important for using the internet with Islamic content among urban Muslim teenagers.